2000
DOI: 10.1177/152692480001000109
|View full text |Cite
|
Sign up to set email alerts
|

Fears and Concerns Expressed by Families in the Donation Discussion

Abstract: Previous research has identified specific fears and concerns among the general public about organ and tissue donation. However, little to none of that research has dealt with fears and concerns at the time of the donation discussion. In this study, 180 experienced coordinators ranked the fears and concerns most commonly heard during the donation discussion. They further classified the fears and concerns according to the ease with which they can be addressed. Subsequently, the fears and concerns were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…Concerns about disfigurement need not be an intractable barrier to donation as potential donors and family members may be persuaded by reassurances that physical disfigurement (particularly of the face) is not evident after donation and that a viewing is still possible (9)(10)(11)18). But while the body may not appear disfigured after donation, the very fact that it has been physically altered appears to invoke fears about mutilation and a desire to maintain bodily integrity and bury the body whole.…”
Section: Lawlor Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns about disfigurement need not be an intractable barrier to donation as potential donors and family members may be persuaded by reassurances that physical disfigurement (particularly of the face) is not evident after donation and that a viewing is still possible (9)(10)(11)18). But while the body may not appear disfigured after donation, the very fact that it has been physically altered appears to invoke fears about mutilation and a desire to maintain bodily integrity and bury the body whole.…”
Section: Lawlor Et Almentioning
confidence: 99%
“…But while the body may not appear disfigured after donation, the very fact that it has been physically altered appears to invoke fears about mutilation and a desire to maintain bodily integrity and bury the body whole. These concerns are quite common and appear to be relatively difficult to overcome in the donation discussion (18). This suggests that there is possibly a role for a broader discussion with the public that is concerned not with correcting a deficit of knowledge about transplantation but with respectfully addressing the very real fears and concerns that people may have about this aspect of organ donation.…”
Section: Lawlor Et Almentioning
confidence: 99%
“…The importance of discussing organ donation with family members has been well documented in many studies that concluded that donation rates are, in fact, higher when the deceased individual's wishes are known within the family (Burroughs, Hong, Kappel, & Freedman, 1998;DeJong et al, 1995;DeJong, Franz, Wolfe, Nathan, Payne, & Reitsma, 1998;Radecki & Jaccard, 1997;Riether & Mahler, 1995;Rosel, Frutos, Blanca, & Ruiz, 1999;Siminoff, Arnold, & Hewlett, 2000;Verble & Worth, 2000). However, less than half of all families have held these discussions (DeJong et al, 1995;DeJong et al, 1998).…”
mentioning
confidence: 99%
“…R esearch into the fears and concerns families have about donation and other issues at the time of donation spans a quarter of a century. 1,2 This research has substantiated that certain kinds of fears and concerns act as impediments to consent. At least 2 of those, the fear of the organs being removed before death and the fear of mutilation, have been documented repeatedly.…”
mentioning
confidence: 85%